2019
DOI: 10.1038/s41467-019-13572-w
|View full text |Cite
|
Sign up to set email alerts
|

TRPML1 links lysosomal calcium to autophagosome biogenesis through the activation of the CaMKKβ/VPS34 pathway

Abstract: The lysosomal calcium channel TRPML1, whose mutations cause the lysosomal storage disorder (LSD) mucolipidosis type IV (MLIV), contributes to upregulate autophagic genes by inducing the nuclear translocation of the transcription factor EB (TFEB). Here we show that TRPML1 activation also induces autophagic vesicle (AV) biogenesis through the generation of phosphatidylinositol 3-phosphate (PI3P) and the recruitment of essential PI3P-binding proteins to the nascent phagophore in a TFEB-independent manner. Thus, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 89 publications
(121 reference statements)
4
77
0
Order By: Relevance
“…Both, enhanced lysosomal biogenesis and induction of autophagy promote the ability of cathepsin B deficient macrophages to get rid of ingested bacteria. TRPML3 has also been shown by several groups to be involved in autophagy (30)(31)(32)), suggesting that as described above for TRPML1 it may play similar roles in certain cell types. Evidence for an evolutionary conserved role of TRPMLs in bacterial clearance by macrophages comes from drosophila work.…”
Section: Chapter I: Innate Immune System Macrophagesmentioning
confidence: 67%
“…Both, enhanced lysosomal biogenesis and induction of autophagy promote the ability of cathepsin B deficient macrophages to get rid of ingested bacteria. TRPML3 has also been shown by several groups to be involved in autophagy (30)(31)(32)), suggesting that as described above for TRPML1 it may play similar roles in certain cell types. Evidence for an evolutionary conserved role of TRPMLs in bacterial clearance by macrophages comes from drosophila work.…”
Section: Chapter I: Innate Immune System Macrophagesmentioning
confidence: 67%
“…Retrograde mobilization of the lysosome is induced in a dynein-dynactin manner by TRPML1 and TMEM55B, which interact with C-Jun-amino-terminal kinase-interacting protein 4 (JIP4) ( Figure 6, step 4) [188]. A recent study demonstrated that TRPML1 activation induces biogenesis of autophagic vesicles by generating phosphatidylinositol 3-phosphate (PI3P) and recruiting PI3P-binding proteins to the nascent phagophore [189]. TRPML1 activity is also required for Ca 2+ -dependent centripetal transport of the lysosome towards the perinuclear region in HeLa cells and Cos1 cells, an effect independent of the Rab7-RIPL pathway [78].…”
Section: Lysosome Localization and Movementmentioning
confidence: 99%
“…TRPML1 can regulate various cellular functions such as large particle phagocytosis through lysosomes [96], autophagosome biogenesis [161], elimination of bacterial pathogens through lysosome activation [162,163], bone remodeling in osteoclastogenesis [94], gastric acid secretion [93], and coronary arterial myocytes apoptosis [95]. In addition, the TRPML1 can reduce the enlargement of the lysosome by activating calmodulin [164].…”
Section: Trpmlsmentioning
confidence: 99%